Do academics find it easy to use e-learing tools - Vilakazi, S.; Ebewo, P. (South African Journal of Higher Education, 2025)
To improve the level of instruction and learning, e-learning has the potential to increase knowledge and skills. According to research, most e-learning systems demonstrate a poor understanding of pedagogy and fundamental flaws in their methods of delivering information. This research seeks to identify a pedagogical viewpoint when designing e-learning solutions. In a higher education environment, technology can encourage active participation in the learning process, which is often challenging to manage in traditional lecturing. Technology allows students to pace their learning by providing unlimited access to content. This study explores academics’ perceptions, opinions, and readiness for the acquisition, adoption and implementation of e-learning to support teaching and learning at Orbit TVET College. The primary goals of the study were to examine the e-learning strategies employedExamine the interventions implemented for effective teaching and learning at Orbit TVET College, as well as the various forms of e-learning the College may employ. The study adopted a qualitative approach, using semi-structured interviews to investigate the e-learning methods employed at the College; this included identifying the effectiveness of the methods used, the challenges that the academics are facing and also the support they get from the management of the college. The purposive sampling method was used to develop a sample of the research under discussion. This method selected sample members based on their knowledge and expertise regarding a research subject. The sample frame for this research included 12 respondents from Orbit TVET College in the North West Province, concentrating only on the following groups, three groups consisted of four lecturers in the three campuses of Orbit TVET College, in Brits (64 lecturers), Mankwe (77 lecturers) and Rustenburg (91 lecturers). The interviews were the principal instruments for data collection. The qualitative data gathered were transcribed using Atlas.ti and analysed using thematic analysis. The findings revealed that the academics at Orbit TVET College know about e-learning and the training conducted but e-learning is not effectively used. The system is there but not effective. In order to successfully educate and learn, the academics at Orbit TVET College need to use a variety of instructional e-learning techniques, which is the focus of this study. In order to successfully educate and learn, the academics at Orbit TVET College need to use a variety of instructional e-learning techniques, which is the focus of the study. The primary goals of the study were to examine the e-learning strategies employed, examine the interventions put in place for effective teaching and learning at Orbit TVET college, and also explore the many types of e-learning that the College might employ. The study recommend that it should be mandatory that the academics use the system and further training be provided to all the lecturers working at Orbit TVET.